2010
DOI: 10.1155/2011/765029
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Potential of Aqueous Ethanol Seed Extract of Ziziphus mauritiana against Cancer Cell Lines and Ehrlich Ascites Carcinoma

Abstract: Ziziphus mauritiana (Lamk.) is a fruit tree that has folkloric implications against many ailments and diseases. In the present study, anticancer potential of seed extract of Ziziphus mauritiana in vitro against different cell lines (HL-60, Molt-4, HeLa, and normal cell line HGF) by MTT assay as well as in vivo against Ehrich ascites carcinoma bearing Swiss albino mice was investigated. The extract was found to markedly inhibit the proliferation of HL-60 cells. Annexin and PI binding of treated HL-60 cells indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 41 publications
(38 reference statements)
6
29
1
Order By: Relevance
“…Taking the antiproliferation and apoptosis induction effect into consideration with necrotic effects, the ethanolic extract of Rianthong seeds showed the most potential as an anti-cancer therapeutic. Previous studies have shown Ziziphus species anti-cancer activity mediated via induction of apoptotic cell death in cancer cell lines [13]- [15]. The chloroform extract of Z. jujuba fruit has been reported to cause apoptosis induction effect against hepatocellular carcinoma cells (HepG2) [15], which is in contrast to our findings where both the water and ethanolic seed extracts of all jujube cultivars tested did not affect HepG2 cells.…”
Section: B Detection Of Induced Death Mode By Flow Cytometrycontrasting
confidence: 99%
See 1 more Smart Citation
“…Taking the antiproliferation and apoptosis induction effect into consideration with necrotic effects, the ethanolic extract of Rianthong seeds showed the most potential as an anti-cancer therapeutic. Previous studies have shown Ziziphus species anti-cancer activity mediated via induction of apoptotic cell death in cancer cell lines [13]- [15]. The chloroform extract of Z. jujuba fruit has been reported to cause apoptosis induction effect against hepatocellular carcinoma cells (HepG2) [15], which is in contrast to our findings where both the water and ethanolic seed extracts of all jujube cultivars tested did not affect HepG2 cells.…”
Section: B Detection Of Induced Death Mode By Flow Cytometrycontrasting
confidence: 99%
“…Another study showed that extracts from Z. jujuba fruit induced apoptosis in estrogen receptor alpha (ERα) positive (MCF-7) and ERα negative (SKBR3) breast cancer cells [14]. Similar to our study, the ethanolic extract from seed of Z. mauritiana was demonstrated to cause apoptotic cell death in human promyelocytic leukemia cells (HL-60), human acute lymphoblastic leukemia cells (Molt-4) and human cervical cancer cells (HeLa) without showing toxicity against normal human gingival fibroblast cells (HGF) [13].…”
Section: B Detection Of Induced Death Mode By Flow Cytometrysupporting
confidence: 83%
“…jujuba (Ziziphus jujuba; Miller) might be useful as a natural functional food ingredient with antioxidant activity and phenolic content. It is used as flavoring agent and additive because of the high nutrient content [21,35,54]. jujuba has considerable amount of ascorbic acid and contains compounds such as glycoside, sterol, alkaloid, tannin, saponin, organic acids, amino acids, triterpenoid, flavonoid, carbohydrate and minerals including potassium, iron, calcium, phosphorus and vitamins including A, B and C [32,41,56].…”
Section: Introductionmentioning
confidence: 99%
“…According to Mukherjee et al [27], ethanolic leaf extract of Thuja occidentalis blocks proliferation of A549 cells (lung carcinoma cells) and induces apoptosis in vitro. Anti-cancer potential study of plant extracts adopting Annexin V on Ziziphus mauritiana in vitro against HL-60, Molt-4, and HeLa cancer cell lines [28], algal extract on the AML cell lines HL-60 and MV-4-11 [29], Sutherlandia frutescens (cancer bush) extract on SNO oesophageal cancer cell line [30], Chaetoceros calcitrans extract on human breast cell line (MCF-7) [31], Mikania hirsutissima leaf extract fraction on U87 human glioblastoma cell line [32] and Melilotus officinalis (sweet clover) extract fraction on human TK6 lymphoblastoid cell line [33] were studied and their apoptotic property has been recorded.…”
Section: Apoptosis Using Annexin Vmentioning
confidence: 99%